Pengaruh Identity Based Attachment terhadap Brand Loyalty yang dimediasi oleh Emotion Based Attachment dengan Customer Experience sebagai Moderasi pada Restoran McDonal’s - Anya Aisha Yunanta; Soepatini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effect of identity-based attachment on brand loyalty, mediated by emotion-based attachment and moderated by customer experience in McDonald's restaurants. A quantitative approach using Structural Equation Modeling (SEM) with SmartPLS 3 was employed. Data were collected through an online questionnaire using a Likert scale, involving 145 respondents who had purchased McDonald's within the last three months. The findings indicate that identity-based attachment significantly influences brand loyalty, mediated by emotion-based attachment. However, customer experience does not strengthen the relationship between emotion-based attachment and brand loyalty. The study's limitations include the sample size and distribution. Future research should expand respondent coverage and include additional variables to enhance analytical depth.